The Influence of Human Resource Competencies, Internal Control Systems, Information Technology and Organizational Commitment on the Quality of Government Financial Reports - Cris Kuntadi; Galih Cheria Puspita (Dinasti International Journal of Education Management And Social Science, 2023)
The Government Financial Report is a financial report prepared by the Government in the context of transparency and accountability for the implementation of the State Budget. The Government Financial Report is a medium to capture the process that runs from start to finish on the use of public money. Starting from planning, budgeting, spending, supervision, to accountability. Therefore, it is necessary to increase the role of government financial reports in the preparation of the state financial management cycle. So that financial reports can be utilized properly by stakeholders, the quality of these financial reports must always be improved. This article reviews the variable influence of Human Resources Competence (X1), Internal Control System (X2), Information Technology (X3), and Organizational Commitment (X4) as independent variables, on the Quality of Government Financial Statements (Y) as the dependent variable. The writing of this article aims to build hypotheses of influence between variables so that they can be utilized in subsequent research. The results of the writing indicate that there is an influence of the variables of Human Resources Competence, Internal Control System, Information Technology, and Organizational Commitment on the Quality of Government Financial Statements.